The Corporate Legal Responsibility for The Leak of Personal Data of Application Consumers in Indonesia - Gesa Bimantara; Tri Astuti Handayani; Muhammad Ainul Yaqin Al Irsyad (JURNAL AKTA, 2024)
The importance of using identity in the form of personal data in all activities related to the fulfillment of rights encourages someone to provide personal data information. Voluntary and mandatory giving is a shame for individuals who seek more profit by using someone's personal data without the permission of the owner of the personal data concerned. The scope and formulation of this research problem focuses on the use of personal data without permission which can be qualified as a criminal offense and what criminal responsibility there is for perpetrators who use personal data without permission. The method used in this writing is the juridical-normative-conceptual legal research method. Research shows that the use of personal data without permission is a criminal offense by fulfilling the elements of general criminal regulations and related special regulations below. In Indonesia, criminal responsibility for perpetrators still does not have specific regulations regarding the imposition of criminal sanctions, so that responsibility is contained in separate regulations. The separate regulations contain several aspects of the protection of a person's personal data in general. The imposition of a crime against a corporation and/or its management does not preclude the possibility of a criminal being imposed on other perpetrators who, based on the provisions of the Law, are proven to be involved in the crime. Based on this research, the government, as the protector and guarantor of citizens' rights regarding the importance of personal data, must immediately ratify the Draft Law on Personal Data Protection for the sake of legal certainty.